1988
DOI: 10.1029/gl015i003p00253
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric traveling convection vortices observed near the polar cleft: A triggered response to sudden changes in the solar wind

Abstract: Analysis of 20‐second resolution magnetometer data from an array of temporary stations operated around Søndre Strømfjord, Greenland during the summer of 1986 shows the signatures of localized ionospheric traveling convection vortices. An example of an isolated event of this kind observed near 08 local time is presented in detail. This event consists of a twin vortex pattern of convection consistent with the presence of two field‐aligned current filaments separated by about 600 km in the east‐west direction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
173
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 331 publications
(188 citation statements)
references
References 14 publications
13
173
2
Order By: Relevance
“…A large portion of MIEs result as the magnetic signature of ionospheric traveling convection vortex (TCV) events as first demonstrated by Friis-Christensen et al (1988) and Glassmeier et al (1989). Potentially, MIEs can be caused by any of a long list of processes in the outer magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…A large portion of MIEs result as the magnetic signature of ionospheric traveling convection vortex (TCV) events as first demonstrated by Friis-Christensen et al (1988) and Glassmeier et al (1989). Potentially, MIEs can be caused by any of a long list of processes in the outer magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…As is evident from the analysis of the rotation of the convection vectors [see Fig. 4 of Friis-Christensen et al (1988)], the centres of the twinconvection vortex system pass just overhead the stations SKT and DYB at 1013-1014 UT. The vortex system travels from east to west and the locations of the leading vortex over these stations are marked (large circles) in Fig.…”
Section: Eventmentioning
confidence: 95%
“…This famous event of Friis-Christensen et al (1988), appearing on the cover of the Geophysical Research Letters, was observed over western Greenland between 1005 and 1020 UT on 28 June 1986. As is evident from the analysis of the rotation of the convection vectors [see Fig.…”
Section: Eventmentioning
confidence: 99%
See 2 more Smart Citations